Using Low Level Laser (LLL for Treatment of Infected Mice with Carcinoma by Activating the Lymph Node Action without Drugs - Khaleel, A.Z.; Albir, A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Regional immune response with mammary gland carcinoma wasstudied statistically. However, the prognostic value remainsconflicting. Thirty mice were used in this study which infectedwere with mammary gland carcinoma. The tumor size of the animalsunder study were measured before and after laser irradiation by usinga vernier and compared these results were with that of non irradiatedanimals with laser (control group)The aim of this study was to evaluate the effect of low level lasertherapy (LLLT) on increasing the response of immune system bystimulating the lymph node action to decrease the cancer cell activityand then decreasing the tumor size of an infected mice.The results of the gross observations showed enlargement in theirradiated lymph node in comparison with that of non irradiated ones.It could be said that the enlargement which occurred to this lymphnode proved that there was an increase in immune response by usinglaser stimulation.From this study, it can be concluded that the LLLT was an efficienttool in stimulating the defense cells found in the lymph node thatattack the cancer cellslocally. The result of this phenomenondemonstrates the decrease of the tumor size of the irradiated infectedmiceIntroductionLymph nodes are encapsulated spherical or kidney-shapedorgans. The nodes are found in the axilla and the groin, along the great